Maradona and Utopia: social dreaming and the left (foot). - Paz, Mariano (Funes. Journal of narratives and social sciences, 2022)
This article discusses the representation of Diego Armando Maradona in popular culture from the perspective of utopian studies. Analysing the Netflix documentary series Maradona in Mexico (2019) and the film Maradona by Kusturica (dir. Emir Kusturica, 2008), in addition to selected examples from Latin American cultural production such as songs and TV programmes, the article maps the utopian tropes that are often associated with the figure of Maradona, generally represented as a saviour of working and popular sectors of society, and as an emancipatory political figure aligned with left-wing regimes in Latin America.